PERBANDINGAN HASIL BELAJAR DAN DISPOSISI MATEMATIS SISWA BERDASARKAN PERBEDAAN GENDER - Septinila Ashuri; Ninit Dwi Noviastuti; Dwi Yuliana; Arini Salsabila; Ahmad Holili; Imron Fauzi (Didaktika : Jurnal Kependidikan, 2022)
AbstractThis study aims to compare student learning outcomes and mathematical dispositions based on gender differences. The gender referred to in this study is gender, namely male and female. The location of this research is in Curah Pecak Village, Purwoharjo District, Banyuwangi Regency. The method used in this research is a comparative descriptive method with a quantitative approach. The population in this study were all students of class XI SMAN 1 Purwoharjo. Sampling was done by random sampling technique with a sampling technique of 1 male student and 1 female student from each class with a total of seven classes, so that the number of samples was 7 male students and 7 female students. Learning outcomes data were obtained by using documentation in the form of the students' Mid-Semester Examination (UTS). score while the mathematical disposition data were obtained by distributing a mathematical disposition questionnaire. Then the data obtained were analyzed using inferential statistics using the Multivariate Analysis of Variance (MANOVA) method. From the results of hypothesis testing, it was found that there were differences in learning outcomes and mathematical dispositions based on gender differences. Thus it can be concluded that gender differences have an influence on learning outcomes and mathematical dispositions of students in class XI SMAN 1 Purwoharjo so that from these differences researchers can compare the learning outcomes and mathematical dispositions of male and female students. Keywords: learning outcomes; mathematical disposition; gender difference